QUALITY OF LABOR RESOURCES IN RUSSIA: REGIONAL ASPECT - A. A. Shabunova; G. V. Leonidova (Russian Journal of Economics and Law)
The article reveals the issues of labor resources formation, their quality characteristics in Russia and in the definite region - Vovlogda region. Basing on the dara of prediction estimations, the authors show that inmedium-term prospective we can see the reduction of unit weight of working-age population, growth of demographic burden on working-age population. Basing on sociological research, the changes of quality characteristics of working people are shown. The importance of increasing the innovative activity of workers and factors hindering this increase are shown.